MENINGKATKAN HASIL BELAJAR PESERTA DIDIK PADA MATERI KLASIFIKASI MAKHLUK HIDUP MENGGUNAKAN MODEL PEMBELAJARAN KOOPERATIF TIPE STAD - Rayko Hasan (Jambura Edu Biosfer Journal, 2021)
This study aims to obtain an overview of the use of the STAD type cooperative learning model in improving student learning outcomes in the classification of living things. The subject of the study was class VII with 28 students, carried out at SMP Negeri 1 Telaga for the 2017/2018 academic year semester 2 (even). The research variables consist of input variables, namely teachers and students, process variables are STAD cooperative learning models and output variables are student learning outcomes. The preparation stages include asking the principal's permission, conducting interviews with related parties, making learning tools, implementing actions and evaluating. The first cycle of data collection was carried out jointly by the researcher and the observer teacher. Teacher and student activities during the learning process are monitored and assessed using observation sheets in cycle I and cycle II. The results of observations of teacher activities in the first cycle which were categorized as good were 46.15% and 53.84% were categorized as moderate. The results of the observation of student activities in the first cycle which were categorized as good were 40% and 60% were in sufficient category. Student learning outcomes in the first cycle which were declared complete reached 60.71% and those who had not completed 39.28%, while the absorption of students reached 70.10%.